2003
DOI: 10.1021/jp0361327
|View full text |Cite
|
Sign up to set email alerts
|

A Nanoscale Optical Biosensor:  The Long Range Distance Dependence of the Localized Surface Plasmon Resonance of Noble Metal Nanoparticles

Abstract: The elucidation of the long range distance dependence of the localized surface plasmon resonance (LSPR) of surface-confined noble metal nanoparticles is the aim of this work. It was suspected that the linear distance dependence found in CH3(CH2) x SH self-assembled monolayer (SAM) formation was the thin shell limit of a longer range, nonlinear dependence. To verify this, multilayer SAM shells based on the interaction of HOOC(CH2)10SH and Cu2+ were assembled onto surface-confined noble metal nanoparticles and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

33
697
4
5

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 691 publications
(739 citation statements)
references
References 51 publications
33
697
4
5
Order By: Relevance
“…Several interesting characteristics of the long-range behavior were found including (1) the LSPR shift vs SAM thickness is nonlinear; (2) Ag nanoparticles are more sensitive than Au nanoparticles; (3) nanotriangles have larger sensing distances than nanohemispheroids; (4) increasing the nanoparticle in-plane width results in larger sensing distances; (5) decreasing nanoparticle out-ofplane height results in larger sensing distances. 7 Semiquantitative theoretical calculations revealed that the plasmon resonance shift is controlled by the average electromagnetic field over the nanoparticle surface. 7 Similarly, the short-range distance dependence (0-3 nm) of the LSPR nanosensor has been studied using alkanethiol, CH 3 -(CH 2 ) x SH (x ) 2-11, 13-15, and 17), monolayers.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several interesting characteristics of the long-range behavior were found including (1) the LSPR shift vs SAM thickness is nonlinear; (2) Ag nanoparticles are more sensitive than Au nanoparticles; (3) nanotriangles have larger sensing distances than nanohemispheroids; (4) increasing the nanoparticle in-plane width results in larger sensing distances; (5) decreasing nanoparticle out-ofplane height results in larger sensing distances. 7 Semiquantitative theoretical calculations revealed that the plasmon resonance shift is controlled by the average electromagnetic field over the nanoparticle surface. 7 Similarly, the short-range distance dependence (0-3 nm) of the LSPR nanosensor has been studied using alkanethiol, CH 3 -(CH 2 ) x SH (x ) 2-11, 13-15, and 17), monolayers.…”
Section: Introductionmentioning
confidence: 99%
“…7 Semiquantitative theoretical calculations revealed that the plasmon resonance shift is controlled by the average electromagnetic field over the nanoparticle surface. 7 Similarly, the short-range distance dependence (0-3 nm) of the LSPR nanosensor has been studied using alkanethiol, CH 3 -(CH 2 ) x SH (x ) 2-11, 13-15, and 17), monolayers. 8,9 It was found that eq 1 does a remarkably good job of accounting for the short-range LSPR response if one assumes a value l d ) 5-6 nm.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…From a practical perspective, the tunable optical properties of nanostructures make it possible to use these materials in surfaceenhanced spectroscopy, [10][11][12][13][14] optical filters, 15,16 plasmonic devices, [17][18][19][20] and sensors. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Until recently, there were only limited methods for the synthesis of monodisperse, nonspherical noble metal nanoparticles, which meant that the practical applications of these particles were limited. Recent advances in controlled syntheses of spheres, 36,37 rods, [38][39][40] triangular prisms, [41][42][43] disks, [44][45][46] cubes, 47 and branched nanocrystals 48 have improved both the fundamental understanding and practical use of these nanoparticles for sensing and spectroscopic devices.…”
Section: Introductionmentioning
confidence: 99%